2001
DOI: 10.1103/physrevb.64.075202
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of shot noise in degenerate disordered conductors in reduced dimensions

Abstract: Monte Carlo calculations of shot noise power S in one-and two-dimensional Anderson models of a disordered conductor are presented. For quasi-one-dimensional geometry all theoretical results derived from random matrix theory are confirmed in ballistic-to-diffusive, metallic, and weak localization regimes. For two dimensions in the weak localization regime the relation Sϭ 1 3 Gϩ␦S 2e 2 /h with ␦S ϭ0.123 74 is found. In the ballistic-to-metallic and strongly localized regimes both one-and two-dimensional geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Under simple assumptions on the distribution function of Lyapunov exponents, one gets the limiting values for M C both in diffusive and critical (3D) regimes. We will also confirm the validity of Nazarov's theory [15] in diffusive case for higher moments and in 4 d = ; for 2 M = and 1 2 3 d Q D = , , it was already shown in [13] and [14], though less precisely because of smaller system sizes and thus larger disturbing ballistic effects.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Under simple assumptions on the distribution function of Lyapunov exponents, one gets the limiting values for M C both in diffusive and critical (3D) regimes. We will also confirm the validity of Nazarov's theory [15] in diffusive case for higher moments and in 4 d = ; for 2 M = and 1 2 3 d Q D = , , it was already shown in [13] and [14], though less precisely because of smaller system sizes and thus larger disturbing ballistic effects.…”
Section: Introductionsupporting
confidence: 82%
“…It is usefull to plot them as a function of conductivity G, rather than of L. Figure 4 left shows, that in 2D the 2 R only roughly approaches the predicted value, at larger G (smaller W ) the ballistic regime disturbs the conver- Table 2. gence. 2 ( ) R G was shown already in [13]. In order to judge the influence of ballistic, we plot the data also for lower W and L in Fig.5 2 R and 3 R , resp.…”
Section: Diffusive M R Combinations Of M Tmentioning
confidence: 98%
See 1 more Smart Citation
“…Here by the theory only the inequality 1 d f z l holds [2,3] whereas numerical simulations give incompatible results [4]. Our recent finite size scaling calculations of quantum mechanical conductance show that superlocalization takes place also for the states inside the band [5]. We have found that for 2D percolation cluster the geometrical average of g $ |w| 2 scales like in Eq.…”
mentioning
confidence: 84%
“…The simulations were performed on 2D percolation cluster at critical sites concentration p = p c = 0.593 by the finite size scaling technique. The conductance g was calculated with the help of Landauer-Bü ttiker formalism and Green's function technique for increasing size L of square lattice (see [5] for more details of the computation technique). The population of the samples was very large (50000) so the evaluation of conductance distribution was possible (see Fig.…”
mentioning
confidence: 99%